Improving the properties of VTP by incorporating fullerene - Makinudin, A.H.A.; Supangat, A. (Royal Society of Chemistry, 2016)
In this study, fabrication of vanadyl 3,10,17,24-tetra-tert-butyl-1,8,15,22-tetrakis(dimethylamino)-29H,31H-phthalocyanine (VTP):[6,6]-phenyl C71 butyric acid methyl ester (PC71BM) composite nanotubes is proven to be successful. VTP:PC71BM composite nanotubes were fabricated via a layer-by-layer method with the assistance of a templating technique. Field emission scanning electron microscopy (FESEM) images have shown successful infiltration of the VTP solution and the further replication of the template with different morphological properties. Infiltration of PC71BM and replication of VTP nanotubes have led to the improvement of morphological, optical and structural properties. Photo-absorption analysis via a UV-vis spectrometer has shown the remarkable absorption spectra of VTP nanotubes (p-type) as well as a further enhancement after the PC71BM (n-type) is introduced into the pre-synthesized nanotubes. Significant red-shifts in the Q-band and B-band region of the VTP:PC71BM composite nanotubes are observed with the incorporation of PC71BM. Morphological analysis of composite nanotubes with different behavior of infiltration has proven influential towards the optical behavior as well as their structural properties.